Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family - Marin, Ivan (European Journal of Taxonomy, 2020)
Lebbeus sokhobio sp. nov. is described from abyssal depths (3303−3366 m) in the Kuril Basin of the Sea of Okhotsk. The related congeners are deep-water dwellers with a very distant distribution and very similar morphology. The new species is separated by minor morphological features, such as the armature of the rostrum and telson, meral spinulation of ambulatory pereiopods and the shape of the pleonal pleurae. This species is the deepest dwelling representative of the genus Lebbeus and the family Thoridae. A list of records of caridean shrimps recorded from abyssal depths below 3000 m is given.